Optimizing Data Analysis Competencies of Accounting Education Students through the Introduction of the STATA Application - Akib, Ambarwati; Ramadhani, Magfirah Wahyu; Utami, Sri; Utami, Dwi; Majiding, Nurul Chalisa (Outline Publisher, 2025)
The ability to process and analyze statistical data is an essential skill for Accounting Education students, particularly in the preparation of quantitative research. However, most students are still limited to the use of common statistical software, necessitating mastery of more comprehensive applications such as STATA. This community service activity aims to improve students' understanding and skills in using STATA through socialization and practice-based training. The implementation methods included preparation, opening and socialization, core training, group discussions and case studies, evaluation, and preparation of reports and publications. The activity was attended by fifth-semester Accounting Education students at Makassar State University. The evaluation results showed an increase in participants' understanding and ability to operate STATA. This activity had a tangible impact on improving student competency and supporting the implementation of the Tri Dharma of Higher Education, particularly community service. It is recommended that similar training be conducted continuously with more in-depth coverage of statistical analysis material.